Optimization of cultivation conditions of the heterotrophic marine microalga \(Thraustochytrium aureum\) BT6 oriented to exploit bioactive compounds - Thom, Le Thi; Hien, Hoang Thi Minh; Thu, Ngo Thi Hoai; Tam, Luu Thi; Ha, Nguyen Cam; Hong, Dang Diem (Academia Journal of Biology, 2021)
Thraustochytrium is a heterotrophic marine microalgae genus belonging to the Labyrinthula class, Thraustochytriaceae (Thraustochytrids) family. Recently, studied results have showed that some species/strains of Thraustochytrium genus are potential candidates to produce biomass rich in lipid containing high polyunsaturated fatty acid (PUFAs), especially docosahexaenoic (DHA C22: 6 ω-3), carotenoid, extracellular polysaccharides (EPSs) and enzymes which play a crucial role in human health. Therefore, throughout many decades, numerous studies have been conducted in exploiting bioactive compounds, especially PUFAs. Biomass and PUFAs yield of some strains Thraustochytrium spp. depend on environmental conditions. In this paper, the results on the effects of different culture conditions on the growth of Thraustochytrium aureum BT6 (isolated from coastal regions of Binh Thuan in 2010) in 500 mL erlenmeyer flask and 30 L fermentors is presented. Suitable conditions for the growth of strain BT6 were: Bajpai medium, 2% glucose, 0.5% yeast extract, temperature of 20−28 oC, salt concentration 0.5%; and initial algal cell concentration of 2 g/L. The dry biomass, lipid and DHA contents of strain BT6 in 500 mL erlenmeyer flasks and 30 L fermentor reached the highest levels of 8.56 ± 0.12 and 6.92 ± 0.27 g/L, 18.36 ± 1.15 and 5.50 ± 0.133% DCW, 2.00 ± 0.05 and 0.14 ± 0.01% DCW, respectively, after 4 days of cultivation. Carotenoid content in flask and 30L fermentor achieved 44.45 ± 1.4 and 28.84 ± 1.12 mg/kg DCW, respectively after 4 days of cultivation. Obtained results have indicated that the algae biomass met the requirements in orientation to exploit valuable bioactive compounds.